CULTURAL HERITAGE AS A BASIS FOR DEVELOPMENT OF TOURISM (AS EXEMPLIFIED BY A SMALL TOWN IN CENTRAL EUROPE) - Bakota, Daniel; Płomiński, Arkadiusz; Rzętała, Mariusz (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The purpose of the study has been to identify the elements of cultural heritage of Hasids in Lelów. A landscape heritage inventory method has been used and a variety of attractions and objects have been identified attributed to traces of everyday life of David Biderman's dynasty Hasids. Attractions from among seven groups of physical classification were identified, namely: environmental objects; archaeological objects; monuments of architecture and urban planning; historical places of remembrance; museums, archives and collections; folk culture facilities and centres; and modern facilities (established after 1945), including events. In addition to the landscape heritage inventory an interview was also used to obtain information. It was found that the core of local and regional tourist product is the annual pilgrimage of Hasids to the tzadik David Biderman's grave, which is the largest and most glaring proof of Lelów's multiculturalism, similarly to the festival of Polish and Jewish culture (Festival of Ciulim and Cholent) organized since 2003. Cultivating traditions of this lineage in the annual celebrations involving thousands of foreign guests is unique on the scale of Central Europe, or at least Poland, a cultural and social event, stimulating the development of tourism.